2013
DOI: 10.1016/j.sjbs.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Free radical scavenging activity, total phenolic content, total antioxidant status, and total oxidant status of endemic Thermopsis turcica

Abstract: Thermopsis turcica, endemic to Turkey, is in danger of extinction. Studies on this species are very few due to the fact that it was only discovered in 1983 and grows in a small circumscribed area in Turkey. In this study, free radical scavenging activity, total phenolic content, total oxidant status (TOS), and total antioxidant status (TAS) of methanol (TTM) and acetone (TTA) extracts of T. turcica were measured spectroscopically. Free radical scavenging activity was determined according to the elimination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(124 citation statements)
references
References 21 publications
6
106
1
3
Order By: Relevance
“…The highest radical scavenging activities could be enlightened with the presence of higher phenols level in P. speciosa. These results are in good accordance with literature, which showed that there is a positive correlation between phenolics content and radical-scavenging activity 37,38 . From these results, phenolics and flavonoids could be considered ones of the main responsible for the hydrogendonating properties of tested extracts.…”
Section: Biological Activitiessupporting
confidence: 93%
“…The highest radical scavenging activities could be enlightened with the presence of higher phenols level in P. speciosa. These results are in good accordance with literature, which showed that there is a positive correlation between phenolics content and radical-scavenging activity 37,38 . From these results, phenolics and flavonoids could be considered ones of the main responsible for the hydrogendonating properties of tested extracts.…”
Section: Biological Activitiessupporting
confidence: 93%
“…From cancer to immune system decline to ageing, antioxidants as vitamins, carotenoids, phenolic compounds, all have disease preventive capacity (Aksoy et al, 2013). By improving or enhancing the proliferation of T-Lymphocyte cells, antioxidants help in fighting off bacterial, viral, fungal infections.…”
Section: Discussionmentioning
confidence: 99%
“…The process associated with the inflammatory response are complex but important aspects which have been exploited for screening of anti-inflammatory compound the role played by Reactive Oxygen Species (ROS) (Aksoy et al, 2013;Laupattarakasem et al, 2003). Discovery of potent Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) with very low or no gastrointestinal (GI) side effects is area of significant interest (Grover et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The free radical scavenging activities of coffee depend on the structural conformation of antioxidant compounds and the ability of these compounds to lose hydrogen. The DPPH free radical, can receive easily an electron or hydrogen from antioxidant molecules to become a stable diamagnetic molecule (Aksoy et al, 2013).The DPPH radical scavenging percent of Nescafé red mug, Turkish coffee and Espresso were 45.6 %, 28.7 % and 23.6 %, respectively. The results showed that there were significant decreases (p<0.01) in scavenging activity in Turkish coffee and Espresso compared to Nescafé red mug (figure 3).…”
Section: Determination Of Dpph Radical Scavenging Activitymentioning
confidence: 98%